SISTEM INFORMASI ASET BERORIENTASI OBJEK - Dadi Rosadi; Dewi Lokayati (STMIK Mardira Indonesia, Bandung, 2015)
An educational institution need of all the assets to support its activities. Assets, include Fixed Assets and Current Assets. Both assets must be managed properly since submited to the deletion process. Current asset management in STMIK Mardira Indonesia still done manually. Based to the important of the role of assets in supporting the activities in this research, tryes to design and implement Information Systems Object-Oriented Processing Assets. This Information Systems Object-Oriented Asset was limited to the process of submission of goods, purchase of goods, receipt of goods, distribution of goods, mutation and deletion process of inventory items and consumables. Information Systems Object-Oriented Asset Processing was developed through analysis using use case model, which is implemented in the PHP programming language and Java Script EXTJS version 2.2 with the MySQL database version 5. Through programming tools, it is expected that information systems can be applied easily operated and provides added value in the management of assets in STMIK Mardira Indonesia. Key Word : system, information, object, fixed asset, curent asset.